Vulnerable communities : research, policy, and practice in small cities - Connolly, James J., 1962-; Faulk, Dagney Gail, 1969-; Wornell, Emily J., 1983- (Cornell University Press, 2022)
"Scholars consider the present condition and future prospects of smaller US cities and towns struggling in the face of broad economic and social change. They offer a mix of ground-level analyses and more general examinations of the successes and failures of recent redevelopment policies and offer concrete ideas for local leaders engaged in redevelopment work"--